Plant in vitro Culture Technologies; A Promise Into Factories of Secondary Metabolites Against COVID-19 - Khan, Tariq; Khan, Mubarak Ali; Karam, Kashmala; Ullah, Nazif; Mashwani, Zia-ur-Rehman; Nadhman, Akhtar (Frontiers in Plant Science, 2021)
The current pandemic has caused chaos in the world. With no vaccines available, there are trials underway for few candidates in humans to find a better alternative against COVID-19. Along with synthetic chemical compounds, phytochemicals cannot be overlooked as candidates for drugs against Severe respiratory coronavirus 2 (SARS-CoV-2). The important role of secondary metabolites or phytochemical compounds against coronaviruses has been confirmed by important studies that reported the anti-coronavirus role of Glycyrrhizin from the roots of Glycyrrhiza glabra. The study demonstrated that Glycyrrhizin is a very promising phytochemical against the SARS-CoV, which caused an outbreak in 2002-2003. Similarly, there are many phytochemical compounds (apigenin, betulonic acid, reserpine, emodin, etc.) isolated from different plants such as Isatis indigotica, Lindera aggregate, and Artemisia annua were employed against SARS-CoV. However, owing to the geographical and seasonal variation, there is less uniform quality of standard medicinal compounds isolated from plants. Furthermore, many of the important medicinal plants are either threatened or on the verge of endangerment because of overharvesting for medicinal purposes. Therefore, plant biotechnology provides a better alternative in the form of in vitro culture technology, including plant cell cultures, adventitious roots culture, organ, and tissue culture. In vitro cultures can serve as factories of secondary metabolites/phytochemicals that can be produced in bulk and uniform quality in the fight against COVID-19, once tested. Similarly, environmental and molecular manipulation of these in vitro cultures could provide engineered drug candidates for testing against COVID-19. The in vitro culture-based phytochemicals have an additional benefit of consistency in terms of yield as well as quality. Nonetheless, as the traditional plant-based compounds might prove toxic in some cases, engineered production of promising phytochemicals can bypass this barrier. Our article focuses on reviewing the potential of the different plant in vitro cultures to produce medicinally important secondary metabolites those could ultimately be helpful in the fight against COVID-19.